2017
DOI: 10.1016/j.biopsych.2016.03.2107
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Induced Retrograde Amnesia of Associative Memories After Neuroplastin Ablation

Abstract: Neuroplastins are essential for learning and memory. Retrograde amnesia after an associative learning task can be induced by ablation of the neuroplastin gene. The inducible neuroplastin-deficient mouse model provides a new and unique means to analyze the molecular and cellular mechanisms underlying retrograde amnesia and memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
115
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(124 citation statements)
references
References 44 publications
8
115
1
Order By: Relevance
“…Long-term potentiation in the hippocampal CA1 region is a better model for studying synaptic plasticity. In this study, we first confirmed that Np65 KO mice exhibited impaired maintenance of LTP, consistent with previous reports in which incubation with Np65-Fc fusion protein or Np65 antibody in hippocampal slices impairs the maintenance of LTP or impaired LTP in Nptn-deficient mice [6,24]. Furthermore, previous reports show that Np65 exerts multiple effects on glutamatergic and GABAergic synapses [7,8].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Long-term potentiation in the hippocampal CA1 region is a better model for studying synaptic plasticity. In this study, we first confirmed that Np65 KO mice exhibited impaired maintenance of LTP, consistent with previous reports in which incubation with Np65-Fc fusion protein or Np65 antibody in hippocampal slices impairs the maintenance of LTP or impaired LTP in Nptn-deficient mice [6,24]. Furthermore, previous reports show that Np65 exerts multiple effects on glutamatergic and GABAergic synapses [7,8].…”
Section: Discussionsupporting
confidence: 91%
“…Finally, Np65 KO mice exhibited [25] reported that Nptn ablation in glutamatergic neurons (Nptn lox/lox Emx1Cre mice) did not disturb formation of spatial memory but showed the discontinuity of swimming action with repetitive pause-swimming cycles and the swimming strategy in reversal probe test. They also reported reduced PMCAs in Nptn À/À mice, inducible Nptn KO mice and Nptn lox/lox Emx1Cre mice, which may be correlated with the altered behaviors [24,25]. The behavioral differences between Np65 KO and Nptn KO mice may be due to these two mouse models having different genetic deletions.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Two isoforms of neuroplastin, Np55 and brain‐specific Np65, have been described . Neuroplastin functions in several vital processes in the mammalian central nervous system including neurite outgrowth, regulation of synaptic plasticity, long‐term potentiation, maintaining balance between the excitatory and inhibitory pathways and the formation of associative memory . Data from mice and rats have allowed us to determine that neuroplastin has a high preference for the hippocampus and cerebellum, but only two studies have systematically analysed Np expression in human brains .…”
Section: Introductionmentioning
confidence: 99%
“…long-term potentiation, 7,8 maintaining balance between the excitatory and inhibitory pathways 9 and the formation of associative memory. 10 Data from mice and rats have allowed us to determine that neuroplastin has a high preference for the hippocampus and cerebellum, 11,12 but only two studies have systematically analysed Np expression in human brains. 3,11 As with other CAMs, it is presumed that Np is involved in the molecular events which underlay the structural and functional processes of brain development, ageing, and neurodegeneration.…”
mentioning
confidence: 99%